The process of multiplication and making words in the language - Mohammed, Sozan; Barzo, Omed (Humanities Journal of University of Zakho, 2022)
The title of the research is about (the process of multiplication and making words in the language), The main purpose of this research is to show the multiplication operations in language levels on the one hand and from the point of view of language schools on the other hand, We also talk about models, processes, word-making laws, word merging, and the process of merging with the tool of the Khanaqi dialect, which is one of the underlying Kurmanji dialects of the Kurdish language, The tool and examples are taken from the everyday speech of the current speakers of the Khanaqi dialect, In this research, the analytical method was used.